Suspension of Care for Patients With Spasticity During COVID-19 Pandemic: Ethical and Medico-Legal Point of View Starting From an Italian Study - De Donno, Antonio; Acella, Adriano; Angrisani, Carmelinda; Gubinelli, Giulia; Musci, Gianluca; Gravili, Gianluca; Ciritella, Chiara; Santamato, Andrea (Frontiers in Medicine, 2021)
The COVID-19 pandemic has revolutionized the habits of entire communities, having even more profound negative effects on assistance for the chronically ill. The sudden demand for extraordinary resources caught all worldwide countries unprepared, highlighting shortages in provision of care services. This applies to all patients, affected by COVID-19 or not, as many need continuing access to chronic diseases treatments. Almost all of the energy available has been directed toward care of COVID-19 patients, and almost nothing has been done to continue therapy for patients with spasticity. This study builds on a recent article and discusses its results as a basis for highlighting the ethical dilemmas and unintended consequences of health systems changing their priorities during the pandemic. The above mentioned study has shown increased patient-perceived spasticity during lockdown (72.2%) with reductions in perceived quality of life (70.9%). Telemedicine tools have proved insufficient, with access by only 7.3% of these patients. Despite the health emergency, it cannot be denied that this situation is a violation of these patients' rights and dignity. The healthcare system will also have to bear increased costs in the future to recover the loss of previous therapies benefits, because of their interruption. The real challenge will be to exploit the critical issues emerged during the pandemic, and to resolve the measures needed to take the care to the patient, and not vice versa. This applies particularly to fragile patients, to respect their dignity and right to care.